Towards a better understanding of the forming and resistive switching behavior of Ti-doped HfOx RRAM. Issue 15 (18th March 2022) - Athena, Fabia F.; West, Matthew P.; Hah, Jinho; Hanus, Riley; Graham, Samuel; Vogel, Eric M.
Abstract : Optimum Ti doping provides a trade-off between the forming voltage and the switching window. A physical explanation of the observed forming and resistive switching characteristics has been provided. Abstract : HfO x -Based resistive random-access memory (RRAM) devices are being widely considered as both non-volatile memories for digital computation and synaptic memory for neuromorphic computing applications. The resistive switching mechanism in these materials is known to be highly dependent on the presence of oxygen vacancies and other dopants. In this work, HfO x is doped with titanium using sequential atomic layer deposition (ALD) of HfO x and TiO x . An increase in the titanium dopant content results in a decrease of the forming voltage, a decrease of both allowable set and reset stop voltages, and a decrease of the high resistance state (HRS) of the RRAM. The physical mechanisms responsible for these observed behaviors are proposed.